Firms' subjective uncertainty and forecast errors: survey evidence from Japan. Issue 1 (2nd January 2023) - Morikawa, Masayuki
ABSTRACT: Using original survey data linked with the financial statements of Japanese listed firms, this study presents an ex post evaluation of firms' ex ante subjective uncertainty. Ex ante forecast uncertainty in terms of sales and employment growth is derived from firms' subjective confidence interval around their point forecasts. Ex post forecast error is calculated as the deviation of the realized figures from the point forecasts. The results indicate that ex ante subjective uncertainty has a significant positive association with realized absolute forecast error. The subjective confidence interval for a firm's own business forecast, in comparison with that for macroeconomic variables, is reliable as a measure of uncertainty. These findings indicate that the subjective probability distribution of business outlook captured by firm surveys contains valuable information for measuring economic uncertainty at the micro-level.